2017
DOI: 10.1021/acs.jpcc.7b00214
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Understanding of Zeolite Nanosheets for Water Desalination

Abstract: Reverse osmosis constitutes a large portion of currently operating commercial water desalination systems. Employing membranes with large water fluxes while maintaining high salt rejection is of central importance in decreasing the associated energy consumption and costs. The ultrathin-film nature of zeolite nanosheets and their versatile pore structures provides great opportunities in desalination. To push forward the development of zeolite nanosheets for water desalination, nonequilibrium molecular dynamics s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 88 publications
(122 reference statements)
1
40
0
Order By: Relevance
“…Water flux was insensitive to toluene over a wide concentration range (10-220 mg L À1 ), but decreased rapidly when cation concentrations in the feed increased. Although computer simulations have predicted many zeolites with high salt rejection and water permeation, 70 their true performances need to be carefully investigated, because water transport inside zeolite membranes is a complex process highly influenced by many factors such as hydrophilicity and surface barriers. 71 In another study, zeolite-coated mesh films for oil-water separation were fabricated by growing the crystals of silicalite-1 on stainless-steel meshes through a seeding and secondary growth process under hydrothermal conditions (Figure 9).…”
Section: Water Purificationmentioning
confidence: 99%
“…Water flux was insensitive to toluene over a wide concentration range (10-220 mg L À1 ), but decreased rapidly when cation concentrations in the feed increased. Although computer simulations have predicted many zeolites with high salt rejection and water permeation, 70 their true performances need to be carefully investigated, because water transport inside zeolite membranes is a complex process highly influenced by many factors such as hydrophilicity and surface barriers. 71 In another study, zeolite-coated mesh films for oil-water separation were fabricated by growing the crystals of silicalite-1 on stainless-steel meshes through a seeding and secondary growth process under hydrothermal conditions (Figure 9).…”
Section: Water Purificationmentioning
confidence: 99%
“…The structures of the ionic LC compounds that form the sub-nano channels are flexible and are involved in strong electrostatic interactions with water molecules. These features of LC membranes are not seen in hard materials that have been considered for use as water treatment materials, such as zeolite [30][31][32] and CNTs. [13][14][15][16][17][18][19][20] Elucidating how each of these features affects the permeability of water molecules and ions in sub-nano channels will contribute greatly to elucidating the factors that determine the water treatment performance.…”
Section: Introductionmentioning
confidence: 99%
“…14 With the aid of zeolite nanosheets, permeability as high as 1.3 L/cm 2 day MPa can be obtained. 15 Recent studies have shown that MoS 2 nanopore filters have the potential to achieve a water permeability of roughly 100 g/m 2 s atm 10 -2 orders of magnitude higher than the commercial RO. This is comparable with that measured experimentally for the graphene filter (∼70 g/m 2 s atm) under similar conditions.…”
Section: Introductionmentioning
confidence: 99%